Predicting Intention to be Physically Active among Volunteer Firefighters. Issue 1 (2nd January 2020) - Amodeo, Kayla L.; Nickelson, Jen
ABSTRACT: Background : Over half of all firefighter deaths are due to heart attacks. Physical activity (PA) is a protective factor against cardiovascular disease, but most firefighters do not meet recommended PA levels. Volunteer firefighters (VFFs), particularly in rural areas, may have unique reasons for not meeting recommendations. Purpose : To examine VFFs' PA intention and factors that might influence it, using the Theory of Planned Behavior. Methods : Using a cross-sectional study design, we surveyed 123 North Carolina VFFs. Results : Most VFFs were overweight (35.9%) or obese (44.4%), and many did not participate in any moderate-intensity cardiovascular (14.4%), vigorous-intensity cardiovascular (40.8%), or strength training (45.2%) exercise in the prior 7 days. On average, participants did not perceive themselves at high risk for heart disease. Regression analyses found that attitudes, perceived behavioral control, and past PA behavior accounted for 57.9% of the variance in PA intention ( p = .031). Discussion : Many firefighters in this study were not meeting recommended PA guidelines and did not perceive themselves at high risk for heart disease. Relationships among variables should be explored more fully by quantitative and qualitative methods. Translation to Health Education Practice : Findings from this study have implications for future PA intervention development aimed at VFF populations.